Fourier series coefficients for a rectified sine wave
Fourier series coefficients for a rectified sine wave
Fourier series coefficients for a rectified sine wave
Create successful ePaper yourself
Turn your PDF publications into a flip-book with our unique Google optimized e-Paper software.
EE 341 Fall 2004<br />
Consider the signal<br />
|sin (ω 1 t)|<br />
sin (ω 1 t)<br />
A<br />
0<br />
−A<br />
A<br />
0<br />
−A<br />
EE 341<br />
<strong>Fourier</strong> Series <strong>for</strong> Rectified Sine Wave<br />
x(t) = A| sin(ω1 t)|<br />
Rectified Sine and Sine<br />
−2 T −T 0 T 2 T<br />
−T1 0 T1<br />
The period of the sinusoid (inside the absolute value symbols) is T1 = 2π/ω1. The period of the <strong>rectified</strong><br />
sinusoid is one half of this, or T = T1/2 = π/ω1. There<strong>for</strong>e,<br />
Thus we can write<br />
The <strong>Fourier</strong> <strong>series</strong> <strong>coefficients</strong> are:<br />
c x k<br />
1<br />
=<br />
T<br />
= 1<br />
T<br />
ω1 = 2π<br />
T1<br />
= π<br />
T<br />
<br />
<br />
x(t) = A <br />
sin T<br />
0<br />
T<br />
0<br />
= ωo<br />
2<br />
<br />
ωo t <br />
2<br />
x(t) e −jkωot dt<br />
<br />
<br />
A <br />
sin <br />
ωo t <br />
e<br />
2<br />
−jkωot dt<br />
From 0 to T , |sin(ωo t/2)| = sin(ωo t/2). Also, replace ωo by 2π/T :<br />
c x k = 1<br />
T<br />
T<br />
0<br />
A sin<br />
<br />
π t<br />
e<br />
T<br />
−j2πkt/T dt<br />
1
EE 341 Fall 2004<br />
c x k = A<br />
T<br />
T<br />
= A<br />
j2T<br />
= A<br />
j2T<br />
= − A<br />
2T<br />
0<br />
T<br />
<br />
ejπt/T − e−jπt/T e<br />
j2<br />
−j2πkt/T dt<br />
<br />
e jπt(1−2k)/T <br />
−jπt(1+2k)/T<br />
− e dt<br />
0<br />
e jπt(1−2k)/T<br />
jπ(1 − 2k)/T<br />
<br />
ejπ(1−2k) π(1 − 2k)/T<br />
T e−jπt(1+2k)/T<br />
−<br />
jπ(1 + 2k)/T<br />
0<br />
+ e−jπ(1+2k)<br />
π(1 + 2k)/T −<br />
1<br />
π(1 − 2k)/T −<br />
<br />
1<br />
π(1 + 2k)/T<br />
But e jπ(1−2k) = e jπ e −j2πk . e jπ = −1 and e −j2πk = 1, so e jπ(1−2k) = −1. Similarly, e −jπ(1+2k) = −1,<br />
so:<br />
For k = 0<br />
c x k<br />
<br />
A −1<br />
= −<br />
2T π(1 − 2k)/T +<br />
−1<br />
π(1 + 2k)/T −<br />
1<br />
π(1 − 2k)/T −<br />
<br />
1<br />
π(1 + 2k)/T<br />
= − A<br />
<br />
−2<br />
2 π(1 − 2k) −<br />
<br />
2<br />
π(1 + 2k)<br />
= A<br />
<br />
<br />
1 1<br />
+<br />
π 1 − 2k 1 + 2k<br />
= 2A<br />
<br />
1<br />
π 1 − 4k2 <br />
T <br />
π t<br />
A sin dt<br />
0 T<br />
= A<br />
T<br />
− cos(πt/T )<br />
T π/T 0<br />
= 2A<br />
π<br />
c x 0 = 1<br />
T<br />
Note: Because the signal is even, you could also find c x k by:<br />
For an odd signal,<br />
c x k<br />
c x k = 2<br />
T<br />
= −j2<br />
T<br />
T/2<br />
0<br />
T/2<br />
0<br />
x(t) cos(kωot) dt<br />
x(t) sin(kωot) dt<br />
2